2017
DOI: 10.1002/pchj.168
|View full text |Cite
|
Sign up to set email alerts
|

Factor analysis of the Swedish version of the Dark Triad Dirty Dozen

Abstract: The aim of this study was to test the proposed three-factor structure of the Swedish version of the Dark Triad Dirty Dozen measure. A confirmatory factor analysis showed mixed evidence for model fit. In contrast to expectations, men did not score significantly higher than women in Machiavellianism and narcissism. Nevertheless, men scored higher than women in psychopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Hence, it is difficult to compare samples. Finally, the results of our confirmatory factor analysis [1] showed that, despite having good correspondence to the English version, there was mixed evidence for model fit.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…Hence, it is difficult to compare samples. Finally, the results of our confirmatory factor analysis [1] showed that, despite having good correspondence to the English version, there was mixed evidence for model fit.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 77%
“… The data include responses to the Swedish version of a brief questionnaire used to operationalize the Dark Triad of malevolent character: Machiavellianism, narcissism, and psychopathy. The data was collected among 342 Swedish university students and white-collar workers (see Garcia et al (2017) [1] ). In this article, we include the Swedish version of Jonason's Dark Triad Dirty Dozen questionnaire.…”
mentioning
confidence: 99%
“…Nonetheless, some of the problems with current Dark Triad research are the unreliable correlations with available models ( Veselka, Schermer & Vernon, 2011 ) and the difficulty on differentiating them from each other ( Garcia & MacDonald, 2017 ). The later probably reflects operationalization problems ( Garcia & Rosenberg, 2016 ; Garcia, MacDonald & Rapp-Ricciardi, 2017 ; Garcia et al, 2017e ; Kajonius et al, 2016 ; Persson, Kajonius & Garcia, 2017a ; Persson, Kajonius & Garcia, 2017b ) that are beyond the scope of the present paper. The former, however, is directly addressed in our study, since the model presented here allows us to conduct analysis of personality as a complex adaptive system–a system that allows the individual to adapt to internal (i.e., different character combinations, which is the focus of our study) and external conditions (e.g., life events and situations) (cf.…”
Section: Discussionmentioning
confidence: 93%
“…were Machiavellianism-agreeableness, narcissism-extraversion, and psychopathy-agreeableness. As a second analysis, we conducted the same analysis between the dark traits and OCEAN controlling for gender, since the dark traits differ between males and females (e.g., Garcia, MacDonald & Rapp-Ricciardi, 2017 ). Nevertheless, the correlations were almost similar (see Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…570 individuals ( n males = 326, n females = 242, and 2 unreported), including university students and white-collar workers with an age range between 19 and 65 years, responded to the Swedish version of the Dark Triad Dirty Dozen ( Garcia et al., 2017a , b ).…”
Section: Methodsmentioning
confidence: 99%